2021
DOI: 10.1016/j.ymthe.2020.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Single and Dual Vector Gene Therapy with AAV9-PHP.B Rescues Hearing in Tmc1 Mutant Mice

Abstract: AAV-mediated gene therapy is a promising approach for treating genetic hearing loss. Replacement or editing of the Tmc1 gene, encoding hair cell mechanosensory ion channels, is effective for hearing restoration in mice with some limitations. Efficient rescue of outer hair cell function and lack of hearing recovery with later-stage treatment remain issues to be solved. Exogenous genes delivered with the adeno-associated virus (AAV)9-PHP.B capsid via the utricle transduce both inner and outer hair cells of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 48 publications
(124 reference statements)
5
58
0
Order By: Relevance
“…However, our results indicate that strong gene editing efficiency is not necessarily required to sufficiently restore hearing in the Kcnq4 W276S/+ murine model; specifically, ~0.6% of gene editing efficiency at the genomic DNA level sufficiently rescued the auditory phenotype with dual AAV plasmids with split SpCas9 and sgRNA. These data are consistent with those of a previous study, which reported sufficient hearing restoration when the in vivo gene editing efficiency was ~0.6% in Beethoven mice harboring the Tmc1 mutant allele 41 . The discrepancy between the efficiency and phenotypic rescue can be explained by several technical reasons.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results indicate that strong gene editing efficiency is not necessarily required to sufficiently restore hearing in the Kcnq4 W276S/+ murine model; specifically, ~0.6% of gene editing efficiency at the genomic DNA level sufficiently rescued the auditory phenotype with dual AAV plasmids with split SpCas9 and sgRNA. These data are consistent with those of a previous study, which reported sufficient hearing restoration when the in vivo gene editing efficiency was ~0.6% in Beethoven mice harboring the Tmc1 mutant allele 41 . The discrepancy between the efficiency and phenotypic rescue can be explained by several technical reasons.…”
Section: Discussionsupporting
confidence: 93%
“…Although these data indicate that in vivo gene editing is applicable for treating AHL caused by the degeneration of OHCs, the efficiency of gene editing and the delivery vehicle used should be further improved. The high-fidelity capsid of AAV, which is optimized for targeting the OHCs, will be required to accomplish these goals; this strategy has improved the transduction rate of AAV9-PHP.B capsid into OHCs 41 , and can therefore be used for further gene editing applications. Moreover, other delivery methods, such as via mRNA and RNP, will be considered to avoid the collateral safety issues associated with administering viral injections to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Toward the clinical application of gene therapy for hereditary hearing loss, TMC1-associated ADNSHL is believed to be a good candidate, as the late-onset and progressive hearing loss phenotype can be stopped or slowed down by gene therapy prior to hearing deterioration. In addition, ENU-induced model mice with the orthologous mutation identified in human ADNSHL patients are widely used for translational research for gene therapy (Askew et al 2015;Shibata et al 2016;Yoshimura et al 2019;Gao et al 2018;Nist-Lund et al 2019;György et al 2019;Wu et al 2021). In most of these gene therapy studies, the gene delivering vector, adeno associated virus (AAV), was administrated into the inner ear of neonate mice, allowing prevention of hearing deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…This mouse model carries the Tmc1:c.1235T > A:p.Met412Lys variant, and subsequent to this report, ADNSHL patients with an orthologous TMC1 variant (TMC1 c.1253T > A:p.Met418Lys) were reported (Zhao et al 2014). As the Beethoven mice showed a similar phenotype (progressive hearing loss with predominant deterioration in the higher frequencies) to human patients and carried the orthologous mutation identified in human ADNSHL patients, this mouse model is widely used for translational research for gene therapy (Askew et al 2015;Shibata et al 2016;Yoshimura et al 2019;Gao et al 2018;Nist-Lund et al 2019;György et al 2019;Wu et al 2021). However, prior to the clinical application of gene therapies, the detailed phenotypes and prevalence information are essential.…”
Section: Introductionmentioning
confidence: 87%
“…The ENU-induced mutagenic mouse model, Beethoven mice, carry the Tmc1:c. 1235 T > A:p.M412K variation, and an orthologous TMC1 variant (TMC1 c.1253T > A:p.M418K) has been reported as causative for DFNA36 (Zhao et al, 2014). Beethoven mice are widely used for translational research for gene therapy and favorable results in the prevention of hearing deterioration in these model mice have been achieved (Askew et al, 2015;Shibata et al, 2016;Yoshimura et al, 2018;Gao et al, 2018;Nist-Lund et al, 2019;György et al, 2019;Wu et al, 2021). In these gene therapy studies, the timing of vector administration is also discussed as most of the studies administrated the gene delivering vector, adeno associated virus (AAV), into the inner ear of neonate mice.…”
Section: Identi Ed Variants Prevalence and The Clinical Features Of Tmc1-associated Hearing Lossmentioning
confidence: 99%